Analysis of Radio Broadcast - Ramadhani, Silviana; Ataqiya, Raihana; Haris, Bakti; Law, Eric; Royi, Jey (Journal International Dakwah and Communication, 2022)
Radio is a public media that conveys the content of its message in the form of information, entertainment, news, and education by audio. In broadcasting, the Radio should have a program that suits the tastes of listeners, has excellent programs, and broadcasters who have their own privileges in communicating with their listeners, as is the case with this Fuad FM radio with some of its program programs that adjust the tastes of its listeners, besides that it does not forget to make its flagship show programs. Therefore, the purpose of this study is to analyze radio broadcast programs in general. The motto used is a qualitative research method. The results obtained from this study show an in-depth analysis of the ins and outs of radio broadcasting, starting from the programs, strategies for creating programs, factors, and others. So, a broadcast program is everything that a broadcasting station displays in the form of sound, image, or sound and image or in the form of graphics, and characters, whether interactive or not, that can be received through a broadcast receiving device to meet the needs of its audience.